Psychologists as 'the quiet ones with the power': understanding indeterminate sentenced prisoners' experiences of psychological risk assessment in the United Kingdom. Issue 6 (2nd July 2020) - Shingler, Jo; Sonnenberg, Stefanie J.; Needs, Adrian
ABSTRACT: Prisoners serving indeterminate sentences in the United Kingdom do not know when or if they will be released from prison. Release and progression decisions are determined by the risk the ISP presents of reoffending. This makes the assessment of risk a high stakes business for ISPs. Whilst there is a large body of literature focused on prisoners' general experiences of prison, there is an absence of specific empirical exploration of prisoners' experiences of risk assessment. This paper aims to address this gap by reporting the results of a qualitative exploration of ISPs' experiences of psychological risk assessment. Interviews with 10 ISPs were conducted and analysed using Grounded Theory methods. Analysis indicated that prisoners experienced the prison environment as characterised by violence, volatility and suffering. Psychological risk assessment is embedded within this emotionally and physically challenging context but also contributes to the experience of suffering. Within this context, prisoners felt s tuck, powerless and out of control in relation to risk assessment, and experienced psychologists as untrustworthy yet powerful . Understanding prisoners' experiences is the first step in resolving some of the long-reported difficulties in working relationships between psychologists and prisoners as well as making the process more procedurally just.